2013
DOI: 10.1186/1477-7827-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin O-acyltransferase (GOAT) is expressed in prostate cancer tissues and cell lines and expression is differentially regulated in vitroby ghrelin

Abstract: BackgroundGhrelin is a 28 amino acid peptide hormone that is expressed in the stomach and a range of peripheral tissues, where it frequently acts as an autocrine/paracrine growth factor. Ghrelin is modified by a unique acylation required for it to activate its cognate receptor, the growth hormone secretagogue receptor (GHSR), which mediates many of the actions of ghrelin. Recently, the enzyme responsible for adding the fatty acid residue (octanoyl/acyl group) to the third amino acid of ghrelin, GOAT (ghrelin O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…In line with this, our group and others have recently demonstrated that GOAT enzyme is overexpressed (at the mRNA and/or protein level) in PCa tissues and PCa cell lines compared to healthy prostate tissues and normal cell lines, and, most importantly, we also reported that GOAT is oversecreted in PCa cells compared to normal prostate cells . In fact, this initial, pilot study from our group revealed that plasma GOAT levels could discriminate between PCa and healthy subjects, suggesting that this enzyme might be used as a potential novel non‐invasive biomarker of PCa .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with this, our group and others have recently demonstrated that GOAT enzyme is overexpressed (at the mRNA and/or protein level) in PCa tissues and PCa cell lines compared to healthy prostate tissues and normal cell lines, and, most importantly, we also reported that GOAT is oversecreted in PCa cells compared to normal prostate cells . In fact, this initial, pilot study from our group revealed that plasma GOAT levels could discriminate between PCa and healthy subjects, suggesting that this enzyme might be used as a potential novel non‐invasive biomarker of PCa .…”
Section: Discussionsupporting
confidence: 85%
“…13 Consequently, these data have led to widespread criticism that PCa is now an "overdiagnosed" and "overtreated" cancer based on the PSA test. Therefore, there is an urgent need for the identification of new diagnostic and prognostic biomarkers for PCa, especially for Sig PCa, in order to improve the clinical management of PCa and to reduce the elevated number of biopsies and the over- In line with this, our group and others have recently demonstrated that GOAT enzyme is overexpressed (at the mRNA and/or protein level) in PCa tissues and PCa cell lines compared to healthy prostate tissues and normal cell lines, 10,21 and, most importantly, we also reported that GOAT is oversecreted in PCa cells compared to normal prostate cells. 10 In fact, this initial, pilot study from our group revealed that plasma GOAT levels could discriminate between PCa and healthy subjects, suggesting that this enzyme might be used as a potential novel non-invasive biomarker of PCa.…”
Section: Discussionmentioning
confidence: 90%
“…As in rats, a 28-amino acid peptide octanoylated at Ser3 is the major active form of human Ghrelin. However, the ratio of circulating desacyl ghrelin to acyl ghrelin is 9: 1 while in the human stomach, the ratio is around 1:3 [26,27].…”
Section: Forms and Derivatives Of Ghrelinmentioning
confidence: 99%
“…The acylation of ghrelin promoted by Ghrelin O-acyltransferase (GOAT) [27] is essential not only for binding with GHS-R1a but also for stimulation of GH secretion [28,29]. Unacylated ghrelin cannot bind and activate the GHS-R 1a and hence is devoid of any effects on endocrine axes.…”
Section: Forms and Derivatives Of Ghrelinmentioning
confidence: 99%
“…Ghrelin mRNA is then translated into preproghrelin, which contains 117 amino acids and can then be acylated and processed into ghrelin and obestatin (Figure 2). Ghrelin- O -acyl transferase (GOAT) is the only enzyme that has been molecularly identified to be able to acylate ghrelin (2628). The ghrelin pro-peptide is cleaved by signal peptidase, prohormoneconvertase 1/3 (PC 1/3) (29), and carboxypeptidase-B like enzyme (18).…”
Section: Ghrelin and Des-acyl Ghrelinmentioning
confidence: 99%